2022
DOI: 10.1186/s40170-022-00300-0
|View full text |Cite
|
Sign up to set email alerts
|

PDK1- and PDK2-mediated metabolic reprogramming contributes to the TGFβ1-promoted stem-like properties in head and neck cancer

Abstract: Background Resistance to chemotherapeutic drugs is a key factor for cancer recurrence and metastases in head and neck cancer (HNC). Cancer stem cells (CSCs) in tumors have self-renewal, differentiation, and higher drug resistance capabilities, resulting in a poor prognosis for patients. In glucose metabolism, pyruvate dehydrogenase kinase (PDK) inhibits pyruvate dehydrogenase and impedes pyruvate from being metabolized into acetyl-CoA and entering the tricarboxylic acid cycle to generate energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Specifically, PDK2 phosphorylates and inactivates PDH, a key enzyme that converts pyruvate into acetyl-CoA to enter the citric acid cycle and generate ATP in the mitochondria [ 19 ]. Growing evidence suggests that PDK2 influences glucose metabolism which is consequently attributed to tumor development [ 20 , 21 ]. Sachiko et al found that high PDK2 expression was associated with a poor prognosis and that inhibiting PDK2 increased cisplatin sensitivity by activating the electron transport chain and increasing the generation of mitochondrial reactive oxygen species in Ovarian clear cell carcinoma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, PDK2 phosphorylates and inactivates PDH, a key enzyme that converts pyruvate into acetyl-CoA to enter the citric acid cycle and generate ATP in the mitochondria [ 19 ]. Growing evidence suggests that PDK2 influences glucose metabolism which is consequently attributed to tumor development [ 20 , 21 ]. Sachiko et al found that high PDK2 expression was associated with a poor prognosis and that inhibiting PDK2 increased cisplatin sensitivity by activating the electron transport chain and increasing the generation of mitochondrial reactive oxygen species in Ovarian clear cell carcinoma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a decreasing energy charge and increasing pyruvate concentrations inhibit PDK activity, thereby leading to increased PDH activation (31). Although several mechanisms, including lactate dehydrogenase-A (LDH-A), hypoxiainducible factor 1A (HIF1A), the AKT-mTOR signaling pathway, and pyruvate kinase M2, are known to control the glycolytic shift in chondrocytes (8, 32-34), PDK is known to mediate the Warburg effectcharacterized by enhanced aerobic glycolysis (35). It may directly lead to the glycolytic shift observed in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages play different roles in pathogen-induced immune responses, tissue repair, and maintenance of homeostasis. Thus, regulating PDK2 to alter macrophage metabolism and influence their activation or polarization has considerable therapeutic potential in cancer and inflammatory diseases ( 37 , 51 53 ). The B7 family co-stimulatory molecule V-set and immunoglobulin domain-containing 4 (VSIG4) are complementary receptors of the immunoglobulin superfamily that are macrophage-specific surface molecules.…”
Section: Regulation Of Macrophage Orientations By Pdkmentioning
confidence: 99%